Women Empowerment Through National Afforestation Programme in Andhra Pradesh (Indian Journal of Extension Education, 2013)
The study was conducted by Regional Centre, National Afforestation and Eco-Development Board, UAS, Bangalore in Forest Development Agency (FDA) of Guntur, Karimnagar, Anantapur, Mahabubnagar and Eluru of Andhra Pradesh to analyse the socio-economic profile, extent of participation and empowerment status of women under National Afforestation Programme (NAP). Majority of the women respondents were middle aged, illiterate and agriculture was the main occupation. The extent of participation of women in FDA activities showed that more than half of the women members (68%) were involved occasionally in nursery activities under afforestation work. Majority of the women members did not attend any kind of workshops, training programmes, demonstrations and educational tour. However, more than three fourth of the women members (78%) occasionally participated in the group discussions. Nearly half of the women, regularly participated in FDA activities, attended the management committee meetings and offered suggestions regularly in the meetings. Empowerment status of women analyzed based on the income generation, employment status and additional employment generation indicated a steady increase in the income level and decrease in unemployment status among the women after joining Vana Samrakshana Samiti (VSS) in forest fringe villages of Andhra Pradesh.